2010
DOI: 10.1121/1.3303977
|View full text |Cite
|
Sign up to set email alerts
|

Coherent reflection without traveling waves: On the origin of long-latency otoacoustic emissions in lizards

Abstract: Lizard ears produce otoacoustic emissions with characteristics often strikingly reminiscent of those measured in mammals. The similarity of their emissions is surprising, given that lizards and mammals manifest major differences in aspects of inner ear morphology and function believed to be relevant to emission generation. For example, lizards such as the gecko evidently lack traveling waves along their basilar membrane. Despite the absence of traveling waves, the phase-gradient delays of gecko stimulus-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 57 publications
5
38
0
Order By: Relevance
“…Preliminary data are provided for wildtype and prestin V499G/Y501H KI mice (referred to here simply as 499) expressing a mutant prestin and showing reduced sensitivity [8]. The SFOAE data from 499 KI mice show loss of sensitivity and no frequency selectivity consistent with previous reports using [2,7], this approach allows us to study the BM-OHC-TM system in young mutant mice and their controls.…”
Section: Introductionsupporting
confidence: 61%
“…Preliminary data are provided for wildtype and prestin V499G/Y501H KI mice (referred to here simply as 499) expressing a mutant prestin and showing reduced sensitivity [8]. The SFOAE data from 499 KI mice show loss of sensitivity and no frequency selectivity consistent with previous reports using [2,7], this approach allows us to study the BM-OHC-TM system in young mutant mice and their controls.…”
Section: Introductionsupporting
confidence: 61%
“…Thirdly, the extension towards higher frequencies appears consistent with a comparison of tympanic membrane velocity response curves in phylogentically matched gecko pairs (Werner et al 2002). Fourthly, SOAEs and low-level SFOAEs rapidly fall off towards the noise floor above the highest ANF characteristic frequencies in Gekko (Manley et al 1996;Bergevin and Shera 2010). Fifthly, SOAE suppression characteristics and SFOAE delays have been shown to correlate well to ANF tuning (Köppl and Manley 1994;Manley et al 1996;Bergevin and Shera 2010).…”
Section: Improved High-frequency Sensitivity In Smaller Lizards?supporting
confidence: 50%
“…Fourthly, SOAEs and low-level SFOAEs rapidly fall off towards the noise floor above the highest ANF characteristic frequencies in Gekko (Manley et al 1996;Bergevin and Shera 2010). Fifthly, SOAE suppression characteristics and SFOAE delays have been shown to correlate well to ANF tuning (Köppl and Manley 1994;Manley et al 1996;Bergevin and Shera 2010). Lastly, ABR audiograms for Anolis carolinensis extend out to higher frequencies relative to Gekko (Brittain-Powell et al 2010), consistent with OAE magnitudes (Manley and Gallo 1997;Bergevin et al 2010b).…”
Section: Improved High-frequency Sensitivity In Smaller Lizards?mentioning
confidence: 57%
See 1 more Smart Citation
“…On the other hand, Bergevin and Shera (2010) showed that a mechanical model of the lizard inner ear, which does not exhibit travelling waves, can model stimulus frequency otoacoustic emissions (SFOAE) in lizards. A further analysis of the model showed that it operates similar to a coherent reflection model of the cochlea.…”
Section: Introductionmentioning
confidence: 99%